Investigating the potential for individually distinctive signature whistles to be used in mark-recapture of common bottlenose dolphins (Tursiops truncatus) - Rashley, Gemma (Department of Oceanography, 2017)
Mark-recapture is used to investigate the abundance, survival and social relationships and even individual-specific habitat use of a number of species. Several studies suggest that individually distinctive acoustic signals could be used in a mark-recapture framework. We investigated the potential of using individually distinctive signature whistles of bottlenose dolphins, Tursiops truncatus. Acoustic and photo identification data were collected simultaneously from a small population of common bottlenose dolphins in Walvis Bay, Namibia, between 2009 and 2015. Visual classification and bout analysis was used to identify signature whistle types. Photos were graded for quality and fins for distinctiveness and matched to a pre-existing catalogue of individuals. Whistle data was graded on signal to noise ratio. Abundance was calculated for both signature whistles and photographic data for the years 2011, 2012 and 2015 separately using Huggins closed models. Since not all animals were used in the photographic mark-recapture and the signature whistles of all animals were not recorded in all encounters, it was necessary to extrapolate mark-recapture estimates up to total population size. Two methods of calculating theta (the proportion detected or 'marked') for acoustic data were investigated, one calculated from the field group size and another based solely on acoustic data. An attempt to match individuals with their signature whistle type was also conducted through a process of encounter matrices and elimination. Assuming that photographic mark-recapture data provides the most accurate measure of population size (2011=65, 2012=82, 2015=83 animals estimated), the acoustic abundance estimate extrapolated using a theta calculated from field group size overestimated the population (2011=131, 2012=243, 2015=133), while the acoustic abundance extrapolated using solely acoustic data gave an underestimation (2011=44, 2012=63, 2015=78). Differences between the acoustic estimates and photo identification estimates were between a 25% decrease and 121% increase. Seventeen signature whistle types were used in the matching process, 3 out of which were confidently matched with individuals and a further 3 were matched through the process of elimination. Overall, this study shows that acoustic abundance estimates using signature whistle data has the potential to provide a conservative estimate of abundance compared to photographic methods. However, estimates were effected by how theta was estimated and further studies to better estimate theta are required to improve abundance estimates from signature whistle data.